Non-ocular tumours following retinoblastoma in Great Britain 1951 to 2004. - MacCarthy, A; Bayne, A; Draper, G; Eatock, E; Kroll, M; Stiller, C; Vincent, T; Hawkins, M; Jenkinson, H; Kingston, J; Neale, R; Murphy, M (2009)
BACKGROUND: Retinoblastoma occurs in both a heritable and a non-heritable form. In the heritable form, there is a predisposition to the development of non-ocular tumours. OBJECTIVES: To identify the types of non-ocular tumour occurring in retinoblastoma survivors and to produce estimates of risk for these tumours. METHODS: We carried out a cohort study that included 1927 cases of retinoblastoma diagnosed in Great Britain between 1951 and 2004. Cases were ascertained through the National Registry of Childhood Tumours and followed up for the occurrence of non-ocular tumours using the routine notification system based on the National Health Service Central Registers in Britain. RESULTS: Of the 1927 cases, 809 were known to have the heritable form of the disease and 1118 assumed to have the non-heritable form. 102 of the heritable and 13 of those classified as non-heritable developed a non-ocular tumour. The cumulative risk of developing such a tumour 50 years after retinoblastoma diagnosis was 48.3% (95% confidence interval: 38.1 to 59.7%) in the heritable and 4.9% (1.9 to 12.4%) in the non-heritable cases. The main categories of non-ocular tumours observed in the heritable cases were soft-tissue sarcomas (36 of which 21 were leiomyosarcoma), osteosarcoma (32), carcinoma (13), brain and central nervous system tumours (10), melanoma (9), leukaemia (4) and others (4). There were a total of 108 non-ocular tumours in 102 cases. CONCLUSIONS: There is a high risk of non-ocular tumours occurring in survivors of heritable retinoblastoma. These results have important implications for the clinical follow-up and counselling of survivors.